Birefringence‐Directed Raman Selection Rules in 2D Black Phosphorus Crystals. Issue 19 (31st March 2016) - Mao, Nannan; Wu, Juanxia; Han, Bowen; Lin, Jingjing; Tong, Lianming; Zhang, Jin
Abstract : The incident and scattered light engaged in the Raman scattering process of low symmetry crystals always suffer from the birefringence‐induced depolarization. Therefore, for anisotropic crystals, the classical Raman selection rules should be corrected by taking the birefringence effect into consideration. The appearance of the 2D anisotropic materials provides an excellent platform to explore the birefringence‐directed Raman selection rules, due to its controllable thickness at the nanoscale that greatly simplifies the situation comparing with bulk materials. Herein, a theoretical and experimental investigation on the birefringence‐directed Raman selection rules in the anisotropic black phosphorus (BP) crystals is presented. The abnormal angle‐dependent polarized Raman scattering of the Ag modes in thin BP crystal, which deviates from the normal Raman selection rules, is successfully interpreted by the theoretical model based on birefringence. It is further confirmed by the examination of different Raman modes using different laser lines and BP samples of different thicknesses. Abstract : Due to the birefringence effect, the polarization of the incident ( e i ) and Raman scattered light ( e s ) engaged in the Raman scattering process of the anisotropic BP crystals are changed (to e i ′, e s ′) when they are traveling in the crystal itself. Thus, the ultimate Raman efficiency (S′) of nonpolar mode deviates from normal Raman selection rule, and should be corrected based on the birefringence effect.